Nanostructured Lipid Carrier: An Approach for Topical Antifungal Drug Delivery - Khare, Pragati; Prasad Rai, Janki (Journal of Neonatal Surgery, 2025)
Nanostructured lipid carriers are the advanced generation of lipid based nanoparticles made by blending of solid lipids with a certain proportion of liquid lipids resulting in less ordered lipid matrix that offer better stability delivery of the carrier molecule. Nanostructured lipid carriers were prepared by using seasame oil as a liquid lipid and piroctone olamine as a carrier. Optimization of nanocarrier was performed by design of experimentation, Box-Behnken design was used in optimization on the basis of three factors. Particle size of piroctone olamine loaded nanostructured lipid carriers was observed 155.7 nm. Optimized formulation was observed stable till the 12 months at room temperature conditions